Meetings or Power Weeks? Boundary Work in a Transnational Police Project - Åkerström, Malin; Wästerfors, David; Yakhlef, Sophia (Qualitative Sociology Review, 2020)
Meetings are common in contemporary working life, but they are often overlooked in academic studies and sometimes defined as empty or boring by employees. Yet, the meeting society is being reproduced again and again. There seem to be hidden ways to incorporate meetings into today’s working life without arousing critique about pointless activities and deviations from what should really be done. One strategy was illustrated in a study of a transnational police project. Police culture celebrates visible crime fighting, which is associated with action, physical toughness, and capturing criminals. The police officers involved in the project emphasized the need to avoid “a lot of meetings,” but de facto constructed their project as meetings. Nonetheless, the project was declared a success. We analyze this paradox in terms of boundary work concerning meetings; the police officers turned some meetings into “real police work” by discursively and practically removing them from the category of bureaucracy and its associations with formalities, rigidity, and documentation. The most important example is how an “operational action group meeting” was renamed “power weeks,” eradicating the very word “meeting” from the term. This was closely associated with increased informality and multi-tasking during these gatherings.